Optimal evaluation of photovoltaic-thermal solar collectors cooling using a half-tube of different diameters and lengths - Maseer M.M.; Ismail F.B.; Kazem H.A.; Wai L.C.; Hadi Al-Gburi K.A. (Elsevier Ltd, 2025)
Photovoltaic Thermal Solar Collectors (PVTs) combine the advantages of photovoltaic (PV) and solar thermal collectors to produce electricity and heat simultaneously. This study proposes a numerical model to investigate the effectiveness of using half-circular tubes to improve thermal conductivity and increase the interaction area between PV panels and tubes. This enhances heat transfer from the PV panels to the working fluid (water) circulating through the thermal absorber. Additionally, the integration of phase change material (PCM) is explored to further boost thermal conductivity and generate hot water. The research focuses on modeling the cooling of solar PV panels using copper half-tubes. The PV panels measure 870 ? 665 ? 3 mm and generate a power output of 100 W. The study examines the impact of key variables such as tube diameter (three standard sizes: 10, 12, and 15 mm) and fluid flow rate (0.008 to 0.04 kg/s). Solar radiation equations are incorporated, and the finite volume approach, implemented in the ANSYS 19.0 software's CFX modeling framework, is used as the underlying methodology. The investigation culminates in an optimization process to determine the optimal operating conditions for the PV system. The results show that the highest electrical efficiency (13.15%) is achieved at a flow rate of 0.04 kg/s for 15 mm diameter tubes and 7 tubes in total. The peak thermal efficiency (74.28%) is observed under the same conditions. In conclusion, this study contributes to the understanding of enhancing PV/T system performance through innovative thermal management strategies and provides valuable optimization recommendations for achieving improved electrical and thermal efficiencies. ? 2023 International Solar Energy Society